Container train operations : introducing competition (B) - Raghuram, G., 1955- (SAGE Knowledge. Cases., 2010)
Container train movement was the monopoly of the Container Corporation of India (CONCOR), a wholly owned subsidiary of Indian Railways (IR). The decision to allow the entry of other players was announced by the Minister of Railways in his budget speech of February 2005. To prepare guidelines for such a policy, RITES, another subsidiary of IR, was awarded the study. RITES submitted its final report in September 2005. The recommendations of the report included entry requirements, classification of routes into various categories based on existing and anticipated traffic volume, regulating entry for each route and minimum traffic commitment by the operators.Subsequent to RITES recommendations, a number of interministerial deliberations took place involving Ministry of Railways (MoR), Planning Commission (PC), Ministry of Commerce and Industry, and Ministry of Shipping. Various aspects of the RITES report were discussed.A final policy statement was released on 5th January, 2006. Fourteen parties subsequently bought licences to run container trains.A next round of meetings was held to finalize the Concession Agreement (CA) between the MoR and container train operators. CA is a legal document that outlines the detailed terms and conditions between parties for the duration of the concession period.This case focuses on what the salient features of the concession agreement should be, given the final policy statement.